Evaluation of the Bilingual Flagship Program at SD IT Brilliant School Bukittinggi - Salsabila, Ayunda; Novita, Lenny; Wati, Yusra; Alfarisyi, M. Iqbal; Ilmi, Darul (Prodi PAI STIT Sunan Giri Bima, 2025)
This study aims to evaluate the implementation of the bilingual flagship program at SD IT Brilliant School Bukittinggi. The bilingual program was adopted as a strategy to enhance students’ foreign language proficiency from an early age. A responsive qualitative approach was employed, utilizing observation, interviews, focus group discussions (FGDs), and document analysis for data collection. The findings reveal that the program has a positive impact on language skill acquisition, particularly in speaking and listening. Teachers adopted active learning methods such as storytelling and role-play. However, inconsistencies in implementation across subjects were observed. Overall, both students and parents responded positively to the program, although challenges such as language anxiety and limited teaching materials were identified. The study concludes that while the bilingual program is fairly effective, improvements are still needed. These include enhanced teacher training, strengthened bilingual curriculum, and greater parental involvement. Periodic program evaluations are recommended to ensure the program’s sustainability and quality improvement.